The combination of WebQual 4.0, LibQual, and Importance Performance Analysis for evaluating the quality of the Universitas Trunojoyo Madura library website - Agustiono, Wahyudi; Prastiti, Novi; Erlinda, Zalina Oktavia (Perpustakaan Universitas Gadjah Mada, 2025)
Introduction. This study evaluates the quality of the Universitas Trunojoyo Madura library website and services The research aims to assess user satisfaction, identify areas for improvement, and provide recommendations to enhance service quality. These findings are essential in ensuring that the library's digital services meet user expectations and needs effectively. Data Collection Method. This study adopts a quantitative approach, using WebQual 4.0 and LibQual methodologies, combined with Importance-Performance Analysis, involving 267 respondents. Data were collected through a structured questionnaire. Data Analysis. The study utilized conformity analysis to compare user expectations with perceived service quality. Gap analysis identified discrepancies between expectations and actual website performance, while quadrant analysis prioritized areas for improvement based on importance and performance levels. Results and Discussion. Findings indicate that the Universitas Trunojoyo Madura library website is generally rated as “Good.” However, gap analysis reveals negative values, suggesting that certain aspects fall short of user expectations. Specific website sections require improvements to enhance usability and effectiveness. Conclusion and Recommendation. While the website’s overall quality is adequate, addressing identified gaps is crucial. Recommendations include optimizing the homepage layout, enhancing the search function, and implementing user-driven adjustments to improve satisfaction and service quality.